1983
DOI: 10.1143/jjap.22.1349
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Photoelectron and Anger Electron Spectroscopic Studies of Chemical Shifts in Amorphous Ge–Se System

Abstract: The chemical shifts of the Ge 3d, 3p3/2,1/2 and Se 3d, 3p3/2,1/2 photoelectron lines were measured for the amorphous Ge–Se system and those of the Ge photoelectron lines are corrected for Auger parameter shifts. According to the valence shell potential model, the ratio of the chemical shift in the amorphous Ge–Se system to that in stoichiometric GeSe2 can be approximated by the ratio of the Ge–Se bond number in the Ge–Se system to that in GeSe2. The chemical shift ratios evaluated from the experimental results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 7 publications
7
21
0
Order By: Relevance
“…The experimental curve can be fitted by a single doublet line located at 53.9 eV whose width (FWHM = 0.97 eV) and energy splitting (0.88 eV) suggest that all the selenium atoms studied have the same chemical state. As expected from the structure and chemical composition of our crystal, the binding energy recorded is within the energy range reported for Se 2− [40][41][42]. Moreover, the description of the Sn 3d peak can also be applied to Se 3d levels since no such data are reported in the literature for SnSe2.…”
Section: Core Levels Studysupporting
confidence: 85%
See 1 more Smart Citation
“…The experimental curve can be fitted by a single doublet line located at 53.9 eV whose width (FWHM = 0.97 eV) and energy splitting (0.88 eV) suggest that all the selenium atoms studied have the same chemical state. As expected from the structure and chemical composition of our crystal, the binding energy recorded is within the energy range reported for Se 2− [40][41][42]. Moreover, the description of the Sn 3d peak can also be applied to Se 3d levels since no such data are reported in the literature for SnSe2.…”
Section: Core Levels Studysupporting
confidence: 85%
“…Moreover, the description of the Sn 3d peak can also be applied to Se 3d levels since no such data are reported in the literature for SnSe2. Ueno's study on germanium chalcogenides reveals a 0.4 eV shift of the Se 3d peak towards higher binding energy when comparing GeSe with GeSe 2 [41]. Applying this observation to tin chalcogenides which are materials with the same symmetry, one may expect that the Se 3d photoemission peak of SnSe 2 will be located at 54.1 eV.…”
Section: Core Levels Studymentioning
confidence: 93%
“…Ge-Se bonds are energetically more favored than GeTe bonds [39] because of Ge having large affinity towards Se due to its higher electro negativity (2.55) than Te. As reported in literatures Ge-Se bonds can form at 30.70, Ge-Se 2 bonds at 31.10, and Ge-Se 3 bonds at 31.20 [40,41] which is consistent with our observations. Segregation of GeSe 2 phase is reported in Ge-Se-Te alloys [18].…”
Section: Xps Analysissupporting
confidence: 94%
“…3(A)c), the Se3d peaks begin to appear at 54.5 inferring Ge-Se bond formation. Earlier reports showed that GeSe and GeSe 2 phases can form at 54.3, 54.50 eV in Ge-Se-Te alloy [40,41]. At 0.50 at.% Se alloy, the observed Se peak shift towards higher BE (56.1 eV) due to the large number of both Ge-Se and Te-Se bonds formation.…”
Section: Xps Analysismentioning
confidence: 86%
“…Shallow CL binding energy spectra from Ce4d were also collected to confirm the VBO values obtained from Ce3d peaks. 29,30 After collecting the binding energy information from each sample surface, the VBO value can be determined by Kraut's method 31 1.…”
Section: Methodsmentioning
confidence: 99%